Design And Validation Of An Interorganizational Information System - Rouibah, Kamel (Asian Academy of Management (AAM), 2006)
This paper presents an interorganizational information system that aims to structure collaboration of engineering activities as well as data sharing across company borders. The paper also describes the approach underlying the system, validates it by designing a system prototype, and tests the system using questionnaire and in-depth interviews in order to further knowledge about the subject. The main results from the test show: collaboration engineering is potentially important for senior managers; end-users were specifically attracted more by the concept rather by its implementation; engineering change management is a complex process; and the support of strategic level is a critical success factor. In addition, the paper describes other factors that emerged during the ongoing project and inhibit success of the system.